Sustainable management and conservation of biota in agricultural soils of the Republic of Moldova - Irina Senicovscaia (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
In present research the ways and methods of the sustainable management and conservation of the soil biota in the modern agricultural ecosystems of the Republic of Moldova are considered. The database of invertebrates, microorganisms and enzymatic activities of different zonal soils in the long-term field experiments has been developed and constantly is updated with a view to the operative evaluation of the degradation processes and ecological effectiveness of the land management. The current status of the biota of arable soils of the Republic of Moldova is characterized by the significant reduction in the abundance, biomass, activity and diversity in comparison with soil's standards that are in conditions of natural ecosystems. The long use of soils in agricultural production led to the imbalance between the processes of decomposition and humus formation and promoted the decrease of soil biota stability and degradation. The values of most soil biological indices decrease in the following sequence: virgin and fallow land - arable land under organic system with farming manure and incorporation of crop residues - arable unfertilized land. A soil management with the involvement of areas with natural vegetation in a crop rotation system created conditions for the improvement of the biota's vital activity in the soil which degraded as a result of a long-term arable use. The recovery rate of the population of Lumbricidae family reaches of 3.0-5.6 worms m-2 per year. Annual increase in the content of microbial biomass in the typical chernozem can be up to 81.3 kg C ha-1 in the layer of the 0-50 cm. The organic farming system greatly improves the enzymatic and humus status of the old - arable soils, but does not restore the biodiversity of invertebrates.
Keywords: 330; soil biota; humus; conservation; organic fertilizer